THE EFFECT OF SALES GROWTH, ASSET GROWTH AND MANAGERIAL OWNERSHIP ON COMPANY PROFITABILITY IN THE PROPERTY AND REAL ESTATE SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2019–2023 - Siti Elan Nisa; Rico Nur Ilham; Wahyuddin; Ghazali Syamni (PT. Radja Intercontinental Publishing, 2025)
The purpose of this study was to determine the effect of sales growth, asset growth, and managerial ownership on company profitability in the property and Real Estate sector listed on the Indonesia Stock Exchange for the period 2019–2023. The data used in this study are secondary data. The population consists of 93 companies, and the sample includes 19 companies selected using purposive sampling, resulting in a total of 95 observations. The data analysis method used is panel data regression. The results show that partially, sales growth has a positive and significant effect on company profitability in the property and Real Estate sector during the 2019–2023 period. Asset growth has a positive but not significant effect on company profitability in the property and Real Estate sector during the 2019–2023 period. Meanwhile, managerial ownership has a positive and significant effect on company profitability in the property and Real Estate sector during the 2019–2023 period.